Taxonomic notes on Acidosasa gracilis and Sinobambusa sulcata (Poaceae: Bambusoideae) - Huang, Yuling; Niu, Zhengyang; Cai, Zhuoyu; Zheng, Xirong; Tong, Yi-Hua; Xia, Nianhe (Phytotaxa, 2024)
Acidosasa gracilis was treated as a synonym of Acidosasa breviclavata in the account of Acidosasa in Flora of China. However, after field study and examination of herbarium specimens, it is concluded that A. gracilis and A. breviclavata are two distinct species. Thus, the name Acidosasa gracilis is reinstated in this study. Besides, this research confirmed that Sinobambusa sulcata is a synonym of A. gracilis, rather than Oligostachyum scabriflorum. A colour plate of A. gracilis and notes on comparison between this species and the morphologically similar species are also provided.